The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1590/s0034-89101985000600008
|View full text |Cite
|
Sign up to set email alerts
|

O internato rural do curso de graduação em nutrição da Universidade Federal de Viçosa (Brasil)

Abstract: RUIZ, T. et al. O internato rural do Curso de Graduação em Nutrição da UniversidadeFederal de Viçosa (Brasil). Rev. Saúde públ., S. Paulo, 19:566-9, 1985.RESUMO: Com a finalidade de se avaliarem os resultados alcançados numa experiência de internato rural, foram analizados os relatórios dos estudantes que dela participaram. Considera-se internato rural a modalidade de estágio que se caracteriza pela transferência do estudanle do "campus" universilário para uma comunidade rural, onde permanecerá por lempo deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Similar activity models were experimented by other national and international Medical Schools and showed significant results (Federal University of Minas Gerais, 2009;Ruiz et al, 1985;Santa-Rosa et al, 2007). The University of Illinois developed a medical education program in rural areas and found that the undergraduate students who experienced it were 14.4 times more prone to choose family medicine and 6.7 times more prone to choose a primary medical specialty.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar activity models were experimented by other national and international Medical Schools and showed significant results (Federal University of Minas Gerais, 2009;Ruiz et al, 1985;Santa-Rosa et al, 2007). The University of Illinois developed a medical education program in rural areas and found that the undergraduate students who experienced it were 14.4 times more prone to choose family medicine and 6.7 times more prone to choose a primary medical specialty.…”
Section: Introductionmentioning
confidence: 80%
“…The disease has impact on health indicators and it is also related to disability and early retirement Pimentel et al, 2011;Magnago et al, 2009;Goldbaum et al, 2005). On the other hand, it is possible seeing the allocation of important public resources aiming at the hospitalization and rehabilitation of hypertensive individuals, since many of them are affected by the disease during their productive life Brazil, 1997;Ruiz et al, 1985). According to the Brazilian Ministry of Health, SAH is a major cardiovascular disease, which has significantly increased in recent years, thus affecting 20 million Brazilian citizens .…”
Section: Discussionmentioning
confidence: 99%
“…Dessa maneira, o aluno executa atividades assistenciais que contribuem para sua legitimação perante a população sem perder de vista a mobilização da comunidade no sentido da conscientização, priorização e busca das soluções dos problemas cotidianos de saúde. 25 Na prática, o Internato Rural objetiva a construção de projeto de integração docente-assistencial que colabora efetivamente para a formação do estudante e a consolidação da qualidade do SUS nos municípios e regiões contempladas por este estágio. Considera-se o Internato Rural como uma das etapas da formação dos alunos, já que os capacita a integrar-se com a equipe multiprofissional e com a comunidade, gerenciar os serviços de saúde, e trabalhar com responsabilidade ética.…”
Section: Discussionunclassified
“…Ao apoiar a residência como uma iniciativa importante para a educação em tempo integral, confirma-se a constatação de que, no momento presente da escola brasileira, o tempo de permanência dos alunos na escola "está muito aquém do que seria necessário para dar conta da formação de nossas crianças e jovens para os desafios do século XXI" (GUARÁ, 2006, p.18 (RUIZ et al, 1985); o histórico do ensino técnico agrícola (SOBRAL, 2009) ou os aspectos fundamentais da educação no campo (THERRIEN E DAMASCENO, 1993). Tais obras nos serviram de referência para a construção deste artigo.…”
Section: Introductionunclassified